1977
DOI: 10.1111/j.1476-5381.1977.tb07506.x
|View full text |Cite
|
Sign up to set email alerts
|

EVIDENCE FOR DOPAMINE DEAMINATION BY BOTH TYPE A AND TYPE B MONOAMINE OXIDASE IN RAT BRAIN in vivo AND FOR THE DEGREE OF INHIBITION OF ENZYME NECESSARY FOR INCREASED FUNCTIONAL ACTIVITY OF DOPAMINE AND 5‐HYDROXYTRYPTAMINE

Abstract: 1 Tranylcypromine (20 mg/kg) administration to rats totally inhibited brain monoamine oxidase (MAO) oxidation of 5-hydroxytryptamine (5-HT), phenylethylamine and dopamine as measured in vitro. When L-3,4-dihydroxyphenylalanine (L-DOPA) (50 mg/kg) was given 30 min after the tranylcypromine, brain dopamine and noradrenaline concentrations rose markedly and the rats displayed characteristic behavioural changes and locomotor activity. 2 Clorgyline (5 mg/kg) administration inhibited 5-HT oxidation by almost 100% bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
72
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(84 citation statements)
references
References 15 publications
10
72
1
Order By: Relevance
“…In agreement with in vivo results of Yang & Neff (1974) and Green et al (1977) who used the whole brain, in the present study it was found that clorgyline rather than deprenyl caused a rise in NA concentrations of hypothalamus, caudate nucleus and the rest of the brain without the latter regions. This rise is even larger when L-DOPA is given to rats in combination with clorgyline, but there is very little change either after (-)-deprenyl alone or (-)-deprenyl plus L-DOPA treatment.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In agreement with in vivo results of Yang & Neff (1974) and Green et al (1977) who used the whole brain, in the present study it was found that clorgyline rather than deprenyl caused a rise in NA concentrations of hypothalamus, caudate nucleus and the rest of the brain without the latter regions. This rise is even larger when L-DOPA is given to rats in combination with clorgyline, but there is very little change either after (-)-deprenyl alone or (-)-deprenyl plus L-DOPA treatment.…”
Section: Discussionsupporting
confidence: 81%
“…After administration of tranylcypromnine, the non-selective MAO inhibitor, the brain NA level also rises to the concentrations seen after the combination of clorgyline and (-)-deprenyl, with a further increase after L-DOPA. These results are very similar to those obtained for the in vivo deamination of 5-HT and dopamine in the rat brain (Green & Youdim, 1975;Green et al, 1977 The present study thus indicates that while in vitro noradrenaline may be deaminated exclusively by MAO A Suzuki et al, 1979;Kinemuchi et al, 1979), when this enzyme form is fully inhibited in vivo, MAO B can continue to act on noradrenaline, albeit at a slower rate, indicating that the affinity of MAO B as compared to MAO A for NA is much lower. These results are not in agreement with the studies of Neff, Yang & Goridis (1973) and others (Goridis & Neff, 1971;Neff & Fuentes, 1976) who reported that noradrenaline was a specific substrate for MAO A alone in the rat brain.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, only a mixed inhibition of type A and type B MAO obtained with pargyline and high concentrations of clorgyline and deprenyl, is able to affect clearly the functioning of the dopaminergic neurones of the rat mesencephalon. It has already been proposed that a complete inhibition of both forms of MAO is required to elevate maximally extracellular dopamine (Butcher et al, 1990;Juorio et al, 1994) and to induce dopamine-related behavioural activation (Green et al, 1977). In order to explain the lack of effects of low concentrations of clorgyline on firing discharge, it is conceivable that the preferential blockade of MAO A by this drug might switch the metabolism of dopamine to extraneuronal non-dopaminergic sites where MAO B still plays an important role (Schoepp & Azzaro, 1982;1983;Butcher et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is evidence that a rather selective inhibition of MAO A can be obtained by a low concentration (nM) of clorgyline while a quite selective MAO B inhibition is caused by (-)-deprenyl treatment (nanomolar range) (Johnston, 1968;Knoll & Magyar, 1972;Harsing & Vizi, 1984). Although it has been demonstrated that the inhibition of MAO with pargyline prevents the formation of 3,4-dihydroxyphenylacetic acid (DOPAC), homovanillic acid (HVA) and increases the efflux of dopamine and 3-methoxytyramine (3-MT) from the striatum of animals pretreated with this drug (Harsing & Vizi, 1984;Imperato & DiChiara, 1984;Kato et al, 1986;Wood et al, 1987;Butcher et al, 1990;Juorio et al, 1994), there are still controversial results about the relative effects of MAO A and B inhibition on dopamine metabolism (Houslay et al, 1976;Green et al, 1977;Schoepp & Azzaro, 1983;Harsing & Vizi, 1984;Juorio et al, 1994 (Engberg et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation